2016
DOI: 10.1039/c6ce00848h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical motion of molecular crystals induced by [4 + 4] photodimerisation

Abstract: The photomechanical bending of crystals of a stilbene-type compound substituted with anthracene and indanone groups, (E)-2-(9-anthrylmethylene)-1-indanone (trans-1), was investigated. When a narrow platelike microcrystal was irradiated with ultraviolet (UV) light at 365 nm, the crystal gradually bent away from the light source and finally reached a semicircular shape after more than 10 min. A larger rod-like crystal, approximately 10 mm in length, also exhibited a slight bending motion. The cessation of UV irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…The projection distance of adjacent BA2DA dimers along the stacking direction is 7.201 Å, while the corresponding anthracene groups in BA2DA is 6.922 Å after geometrical optimization (Figure S21). This result suggested that the crystal length could elongate approximately 4.0 % along the b axis after intermolecular [4+4] photodimerization, which is consistent with our observation in SCXRD measurement . In addition, the bending behavior of BA2DA crystal was reversible by thermal treatment .…”
Section: Figuresupporting
confidence: 89%
“…The projection distance of adjacent BA2DA dimers along the stacking direction is 7.201 Å, while the corresponding anthracene groups in BA2DA is 6.922 Å after geometrical optimization (Figure S21). This result suggested that the crystal length could elongate approximately 4.0 % along the b axis after intermolecular [4+4] photodimerization, which is consistent with our observation in SCXRD measurement . In addition, the bending behavior of BA2DA crystal was reversible by thermal treatment .…”
Section: Figuresupporting
confidence: 89%
“…The[4+ +4] photoreaction of BA2DA can form dimmer, oligomer or polymer.I no rder to simplify the calculation task, we proposed an aggregation model of BA2DA-dimer to explain the experiment results.T he projection distance of adjacent BA2DA dimers along the stacking direction is 7.201 ,w hile the corresponding anthracene groups in BA2DA is 6.922 after geometrical optimization ( Figure S21). [14] In addition, the bending behavior of BA2DA crystal was reversible by thermal treatment. [14] In addition, the bending behavior of BA2DA crystal was reversible by thermal treatment.…”
Section: Angewandte Chemiementioning
confidence: 98%
“…This result suggested that the crystal length could elongate approximately 4.0 %a long the b axis after intermolecular [4+ +4] photodimerization, which is consistent with our observation in SCXRD measurement. [14] In addition, the bending behavior of BA2DA crystal was reversible by thermal treatment. [15] The disappearance of characteristic 1 HNMR signals ascribed to anthracene dimerization ( Figure S14) revealed BA2DA can completely recover after thermal treatment.…”
Section: Angewandte Chemiementioning
confidence: 98%
“…When 6cazpy crystals were irradiated, the intensities of some peaks decreased. For example, the intensity of the peak at 2θ = 4.782 • decreased to 50.6% of the original value (Figure 9a,b), likely due to the trans-to-cis photoisomerization and a corresponding deterioration of crystallinity [21]. The intensity eventually recovered to 64.6% of the original value at 10 min after the UV irradiation was stopped.…”
Section: Mechanism Of Photoinduced Motionmentioning
confidence: 96%
“…Among all the external stimuli, light which can be remotely, instantly and precisely controlled is an attractive source to adjust material properties. Therefore, many photomechanical materials such as azobenzene [11][12][13][14][15], salicylideneaniline [16], diarylethenes [17][18][19], anthracene [20,21], naphthalene diimides [22], furylfulgide [23] and even metal organic complex crystals [24,25] have been investigated for the realization of converting light energy to mechanical motion of bending [11,12], twisting [20,26,27], coiling [28,29], expanding [30], jumping [10] and popping [24].…”
Section: Introductionmentioning
confidence: 99%